Pengembangan Media Smartboard untuk Meningkatkan Kemampuan Mengenal Huruf Siswa Cerebral Palsy di SLB Negeri Lutang: Development of Smartboard Media to Improve Letter Recognition Ability for Students with Cerebral Palsy at Lutang State Special School - Dwiyatmi Sulasminah; Abdul Hadis; Dwi Wulandari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
This study aims to better understand how the use of smartboard media supports letter recognition ability in students with Cerebral Palsy at Lutang State Special School. Data was collected using a questionnaire and an efficacy assessment. Among them are the Lutang State Special School instructor and two examiners. This study describes the development of 4D models: definition, design, development, and dissemination. Quantitative descriptive analysis was carried out on the collected data. The result of the media research validation test for smartboards shows that handwriting recognition in students with Cerebral Palsy is feasible and can be learned.